TRANSFORMATION OF BUSINESS MODELS IN THE CONTEXT OF THE DIGITAL ECONOMY - Ashurov Hoshimjon Otayevich (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
The digital economy has become a key driver of business model transformation across industries. Digital technologies reshape how firms create, deliver, and capture value, leading to the emergence of platform-based and data-driven business models. This study examines the conceptual foundations and key dimensions of business model transformation in the context of the digital economy using a qualitative analytical approach. The findings reveal that successful transformation requires not only technological adoption but also strategic and organizational change. The study contributes to the theoretical understanding of digital business model innovation and provides a basis for future empirical research.